2010
DOI: 10.1016/j.ultrasmedbio.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional High-Frequency Characterization of Cancerous Lymph Nodes

Abstract: High-frequency ultrasound (HFU) offers a means of investigating biological tissue at the microscopic level. High-frequency, three-dimensional (3D) quantitative-ultrasound (QUS) methods were developed to characterize freshly-dissected lymph nodes of cancer patients. 3D ultrasound data were acquired from lymph nodes using a 25.6-MHz center-frequency transducer. Each node was inked prior to tissue fixation to recover orientation after sectioning for 3D histological evaluation. Backscattered echo signals were proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
90
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 36 publications
7
90
0
1
Order By: Relevance
“…Early work in opthamology [1] showed the potential value of analyzing the RF spectrum for diagnostic purposes. Since then, QUS techniques have been successfully demonstrated for use in the prostate [2], breast cancer [3][4][5], and detection of metastases in lymph nodes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Early work in opthamology [1] showed the potential value of analyzing the RF spectrum for diagnostic purposes. Since then, QUS techniques have been successfully demonstrated for use in the prostate [2], breast cancer [3][4][5], and detection of metastases in lymph nodes [6].…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study, our group demonstrated the ability of three-dimensional (3D) quantitative ultrasound (QUS) to characterize lymph-node tissues from cancer patients [4]. Reliable determination of the presence or absence of metastatic cancer in lymph nodes is essential for staging disease and planning its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In routine pathology procedures, our QUS methods would be used to direct the pathologist to suspicious nodal regions that might be overlooked in conventional histology. To achieve this objective, previous QUS studies that were undertaken successfully [4] have been improved, including envelope statistics, and applied to a larger number of lymph nodes to enhance statistical significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies concluded that effective scatterer diameter (ESD) and effective acoustic concentration (EAC) could be used to differentiate between different kinds of tumors. Recently, Mamou et al [24] showed that QUS scatterer size estimates could be used to differentiate between cancerous and cancer-free regions in human patient lymph nodes. The use of envelope statistics combined with spectral features was observed to increase the ability of QUS to detect and classify cancer in rodent models, as well as improve the detection of metastases in the lymph node [25].…”
mentioning
confidence: 99%